The Influence Of Calcite On The Ash Flow Temperature For Semi-Anthracite Coal From Donbas District - Čarnogurská Mária; Příhoda Miroslav; Pyszko René; Širillová Ľubomíra; Palkóci Ján (Chemical and Process Engineering)
This paper presents the results of research focused on the lowering of ash flow temperature at semianthracite coal from Donbas district by means of additive (calcite) dosing. Ash fusion temperatures were set for two coal samples (A, B) and for five various states (samples of ash without any additives, with 1%, with 3%, with 5% and with 7% of the additive) in total. The macroscopicphotographic method was used for identifying all specific temperatures. Obtained outputs prove that A type coal has a lower value of sphere temperature than B type coal in the whole scope of percentage representation of the additive. The flow temperature dropped in total from 1489 °C to 1280 °C, i.e. by 14% during the test of coal of type A with 7% of the additive; while it was near 10% for coal of type B (from 1450 °C to 1308 °C). Numerical simulations of the process showed that it is not effective to add an additive with a grain size lower than 280 μm by means of wastevapour burners.